Agonia „przewodniej siły”. Kryzys PZPR w latach osiemdziesiątych na przykładzie Gdańska i Gdyni - Brzeziński, Piotr (Pamięć i Sprawiedliwość, 2011)
The expiration of the “leading force”: The 1980s PUWP crisis in Gdańsk and GdyniaThe article presents the situation within the Gdańsk party organization towards the end of the communist era based on previously unpublished documents preserved at the State Archives in Gdańsk and their Gdynia section, PUWP Central Committee materials held by the Archives of New Records, as well as secondary literature.This is a case study of the functioning of a local link of the PUWP. The author’s objective was to show selected aspects of the gradual disintegration since the 1980s of the communist party which had held almost absolute power in Poland for four decades. Most of the symptoms of the crisis enumerated in the article subsequently became visible on a national scale, greatly contributing to the fall of the regime in 1989.The establishment of Solidarity in August 1980 shook the foundations of the PUWP, As the first trade union in the soviet bloc to assert independence form national authorities, Solidarity proved a better representative of the workers. Within a short time, almost 10 million Poles had joined Solidarity, including 1 million PUWP members. As a result, the communists were forced into a defensive position.Once again the party leaders decided to use force in defense of their authority. In retrospect, the introduction of martial law by Gen. Wojciech Jaruzelski should be considered the beginning of the end of the PUWP which proved incapable of playing its “leadership role” guaranteed by the constitution. The operation was successful but the patient did not survive—these ironic words aptly describe the situation within the party after December 13, 1981. Bringing out the army into the streets failed to prevent the decomposition of the PUWP.The communists’ electoral defeat of June 4, 1989 served as a strong impulse for accelerating the process of “folding up” the party, “enfranchising the nomenclature,” and transforming the PUWP into a modern organization professing a social-democratic doctrine.